North-South : a programme for survival (London : Pan Publications; Cambridge, Mass. : The MIT Press, 1980)
The first part of this report focus on the contrast between the poverty of many less countries and the present relative affluence of the more developed ones, which can and can only be abated, it is assumed, by the further 'development' former. The focus of the other is on the link between economic development conservation of the planet's living resources.
lje 17/09/2018
Loans
Keywords: Economic development; International economic relations; Developing countries